Carbon Dioxide Water Bathing Enhances Myogenin but Not MyoD Protein Expression after Skeletal Muscle Injury - Ito, Kenichi; Ogaya, Shinya; Kataoka, Masataka; Akiyama, Junichi; Une, Satsuki; Nonaka, Koji; Tatsuta, Naomi; Okuda, Kuniharu; Iwata, Akira (Journal of Physical Therapy Science, 2013)
[Purpose] We reported that carbon dioxide (CO2) water bathing accelerates skeletal muscle regeneration; however, the underlying mechanism was unclear. MyoD and myogenin play roles in muscle regeneration, and the purpose of this study was to determine changes in MyoD and myogenin caused by CO2 water bathing after injury. [Subjects] Sixteen female Wistar rats (n = 4 per group) were used. [Methods] The rats were divided into four groups: no-injury (NI), injury (IC), injury + tap water bathing (ITW), and injury + CO2 water bathing (ICO2). Muscle injury was induced by injection of bupivacaine hydrochloride into the left tibial anterior (TA) muscles. Tap water and CO2 (1,000 ppm) water bathing were performed at 37 °C for 30 minutes once a day. The left TA muscles were removed 4 days after injury, and the expressions of MyoD and myogenin were measured. [Results] MyoD and myogenin were increased in the IC, ITW, and ICO2 groups compared with the NI group. Although the MyoD level was similar in the IC, ITW, and ICO2 groups, myogenin increased more in the ICO2 group than in the IC and ITW groups. [Conclusion] CO2 water bathing after muscle injury appears to induce an increase in the expression of myogenin.